Deffense Offset Policy in Indonesia - Tippe, Syarifudin (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Offset mechanism is a policy of the defense industry sector which had been increasing since 1950. Offset implementation has provided some profit-making such as offset obligations in the United States to encourage exports and offset policy in India that had been increasing since 1959 through the use of modern technology facilities by creating the National Aerospace Laboratories (NAL). On the other hand, Indonesia as one of the pioneers in the implementation of defense offsets is still heavily dependent on the procurement of defense equipment from other countries. Therefore, this study aimed to analyze the implementation of defense offsets in Indonesia and the importance of the defense offset policy in Indonesia. Thus, this study is able to contribute to public policy in Indonesian literature. This study used a qualitative approach to conduct a study in the defense industry with the application of defense -related offsets in Indonesia. The results showed that the low competitiveness of the defense industry is due to the low quality of human resources, lack of research and development programs in the field of defense industry and the lack of legal protection in the defense offset policy.